Modeling the use of common bean (Phaseolus vulgaris L.) traditional varieties and their mixtures with commercial varieties to manage bean fly (Ophiomyia spp.) infestation in Uganda - Ssekandi W.; Mulumba J.W.; Colangelo, P.; Nankya R.; Karungi J.; Otim, M.; Fadda, Carlo; Jarvis, Devra I. (2015)
The common bean, Phaseolus vulgaris, is a vital crop in East and Central Africa serving as a food and cash crop and playing an important nutritional role by providing between 20 and 25% of proteins. Unfortunately bean yields have consistently remained lower than potential yield. One reason being pest and disease damage by bean fly (Ophiomyia spp.) which is the most economically damaging and widely distributed field insect pest of common bean in Uganda. This poster introduces our research on the effectiveness of planting intra-specific common bean mixtures (different varieties together in one field) to reduce the incidence of bean fly infestation. Our research shows that random mixtures are more effective than alternate row mixtures, with the highest decrease in damage registered in random mixtures with at least 50% bean fly resistant varieties.